Service centres in rural India : policy, theory, and practice - Wanmali, Sudhir (B.R. Pub. Corp. ; Distributed by D.K. Publishers' Distributors, 1983)
Study based on a survey conducted in Miryalguda Taluk, Nalgonda District, Andhra Pradesh, 1978/79.